The physiological effect of infertility in women on some sex hormones and thyroid in Tikrit city and it’s surrounded area - Wahbi Abdulqader Salman; Najat Maolod Jasim (Tikrit Journal of Pure Science, 2023)
This research was performed in Tikrit Teaching Hospital from October 2013 until april 2014, to study the  physiological effect of age and body mass Index for infertile women compared with healthy and their impact on the concentrations of FSH, LH, testosterone, estrogen, TSH, T3, T4 hormones. This study included (60), infertile  and healthy (30), women, and the patients and healthy ranged age (16-45) years old. The results were as following, significant in infertile women (P˂0.05) in the concentrations of FSH hormone and high significant  (P˂0.01) in LH, Testosterone, T3,T4 hormones compared with healthy, there is not any significant between infertile and healthy women in TSH hormone concentration ,but there are high significant of estrogen in healthy compared with infertile women. Infertile women have significant (P˂0.05) in LH FSH Testosterone T3 T4 in all age categories and increased concentrations of those hormone with age advance, but healthy women have significant (P˂0.05) in estrogen compared with infertile in all age categories. BMI for infertile women were giving significant (P˂0.05) in FSH compared with healthy in (32-and more) Kg/m2, while there was significant increased (P˂0.05) of LH in the (27-31), (32-and more) Kg/m2 BMI categories in the infertile compared with healthy. All infertile women BMI categories have significant increased (P˂0.05) in Testosterone, T3,T4 hormones compared with healthy. there isn’t any significant seen between infertile and healthy women in all  BMI categories.